The resource-mediated modular structure of a non-symbiotic ant-plant mutualism - Ballarin, Caio S. [UNESP]; Hachuy-Filho, Leandro [UNESP]; Sanz-Veiga, Priscila A. [UNESP]; Amorim, Felipe W. [UNESP] (Wiley-Blackwell, 2019)
1. Plant-animal mutualisms are key processes that influence community structure, dynamics, and function. They reflect several neutral and niche-based mechanisms related to plant-animal interactions. 2. However, the strength with which these processes influence community structure depends on functional traits that influence the interactions between mutualistic partners. In mutualisms involving plants and ants, nectar is the most common reward, and traits such as quantity and quality can affect ant species' responses by influencing their recruitment rates and aggressiveness. 3. In this study, nectar traits that mediate ant-plant defensive mutualisms were manipulated to test whether resource quantity and quality affect the structure of ant-plant interaction networks. A downscaling approach was used to investigate the interaction network between ant species and individual plants of the extrafloral nectary-bearing terrestrial orchid Epidendrum secundum. 4. We found a short-term reorganization of the ant assemblage that caused the interaction networks to become more specialised and modular in response to a more rewarding nectar gradient. Furthermore, the ant species tended to narrow their foraging range by limiting their associations to one or a few individual plants. 5. This study shows that ant species' responses to variable resource traits play an important role in the structure of the ant-plant interaction network. We suggest that more rewarding nectar enhanced aggressiveness and a massive recruitment of some ant species, leading to lower niche overlap and thus a less connected and more specialised network.
Keywords: Ant-plant interactions; modularity; niche-based processes; resource availability; specialisation